ASSESSMENT OF ADOPTION OF GOOD AGRICULTURAL PRACTICES AMONG ARABLE CROP FARMERS IN BORNO STATE, NIGERIA - Aliyu, Y. M.; Kauna, K. M.; Rabiu, M.M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined adoption of Good Agricultural Practices (GAPs) and arable crop cultivation in Borno State, Nigeria, using a multistage sample of 390 farmers. Data were collected from structured questionnaires and analysed with descriptive statistics and logit regression. Results shows that 73.85% of respondents were male, 76.15% married, and 36.15% had tertiary education. The mean age was 43 years, average household size 8, and farm size 3.31 ha. Major cultivated crops were maize (82.56%), bambara nut (76.15%), and groundnut (73.07%). Common GAPs adopted included fertilizer application (80.97%), seed treatment (65.91%), and recommended spacing (64.77%). Logit analysis reveals that farm size, cooperative membership, and access to credit as significant determinants of GAPs adoption. Key constraints to adoption of GAPs were inadequate inputs (78.46%), insecurity (74.62%), poor storage (73.08%), and insurgency (73.08%). The study provides a comprehensive assessment of the socio-economic characteristics, production patterns, adoption of Good Agricultural Practices (GAPs), and the major constraints faced by arable crop farmers in Borno State. Results show that arable crop production is largely male-dominated, with most farmers being married, relatively educated, and operating within medium-sized households that support labor needs. Despite their active involvement in farming, access to key productive resources—particularly credit and extension services—remains markedly low, limiting their capacity to innovate and adopt improved practices. Farmers cultivate a diverse range of arable crops, with maize, Bambara nut, groundnut, and sesame emerging as the most dominant. Adoption of GAPs was moderate to high across several practices, especially fertilizer application, seed treatment, recommended spacing, improved storage, timely land preparation, and clean weeding. Recommendation; Since credit significantly enhances GAP adoption, government, microfinance institutions, and NGOs should establish low-interest, collateral-free credit schemes, strengthen group lending, and integrate financial literacy training to empower farmers to invest in improved technologies. Ensure Adequate and Timely Supply of Agricultural Inputs